Method of operative treatment of valgus deformation of a toe - I. V. Zedgenidze (Acta Biomedica Scientifica, 2013)
Valgus deformation of a toe is the most common orthopedic pathology of a human. This pathology prevails in women, especially of elderly age. According to the data of different authors, the ratio between men and women is from 70—80 % to 20—25 %. Basing on the existing level of technologies of treatment of valgus deformation of a toe increase of effectiveness of treatment due to total correction of the deformation, stronger fixation of osteotomed fragments, especially at the osteoporosis, restoration of full and. painless range of motions in metatarsophalangeal and. interphalangeal joints and. also decrease of a risk of intraoperational fracture of fragments became an objective. We analyzed the results of surgical treatment of valgus deformation of a toe and. varus deformation of toe instep bone in 82 patients of 20—60 years. 92 operations in patients with II—III degree of deformation were carried out. 52 patients with II degree of deformation and. 30 patients with III degree of deformation were operated with use of our method. The article presents the results of treatment of valgus deformation of a toe and. varus deformation of toe instep bone in 82 patients by proposed method. Use of this method allows to eliminate valgus deformation of a toe, to restore congruence in metatarsophalangeal joint with the shift of sesamoid complex, to correct varus deformation. of toe instep bone, to eliminate external rotation of a toe by longitudinal cuneiform osteotomy of proximal fragment on the external surface of a toe instep bone at once. Our surgical method allows to reach strong fixation of the bone fragments after osteotomy especially at the osteoporosis, to restore full and. painful range of motions in metatarsophalangeal and. interphalangeal joints. It becomes possible to have good cosmetic effect and. to improve quality of life of patients.